2022
DOI: 10.1200/jco.2022.40.16_suppl.e24111
|View full text |Cite
|
Sign up to set email alerts
|

Bone-targeting agent utilization among lung cancer patients with bone metastasis in Taiwan.

Abstract: e24111 Background: Bone is a common metastatic site among patients with advanced lung cancer. With new treatments available to improve survival of lung cancer and in all likelihood to change the natural history of disease, the diagnosis and management of bone metastasis (BM) may be of increasing clinical relevance. This study aimed to describe the management of BM using bone targeting agents (BTA) among lung cancer patients in Taiwan. Methods: A retrospective cohort of lung cancer patients with BM from 2004 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Subsequently, denosumab has become the most commonly used BMA in Taiwan. Despite this, not all NSCLC physicians prescribe BMAs to manage bone diseases or SREs [ 21 , 22 , 23 , 24 , 25 ]. In addition, physicians and/or patients often decide to initiate bone treatment upon the occurrence of SREs or later in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, denosumab has become the most commonly used BMA in Taiwan. Despite this, not all NSCLC physicians prescribe BMAs to manage bone diseases or SREs [ 21 , 22 , 23 , 24 , 25 ]. In addition, physicians and/or patients often decide to initiate bone treatment upon the occurrence of SREs or later in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Although bone-modifying therapies have been approved for NSCLC patients with bone metastasis, only around half of NSCLC patients with bone metastasis received BMAs to manage bone diseases or SREs [ 21 , 22 ]. In Taiwan, a recent national-based survey investigated 44,800 lung cancer patients with bone metastasis and reported that BMAs had been prescribed in only 28.4% patients [ 25 ]. In the present study, seventy three (38.4%) patients had denosumab in addition to two receiving other BMAs and 56.1% of seventy three patients started denosumab treatment with or after SRE occurrence ( Table 1 and Figure S1 ).…”
Section: Discussionmentioning
confidence: 99%